EFFORTS TO REDUCE CLIMATE CHANGE IMPACT ON MINING OPERATION PROFITABILITY BY DATA VISUALISATION AND SYSTEM DYNAMICS APPROACH: CASE STUDY PT. BERAU COAL - Febrianto, Ardyan
Climate change effects could come in direct or indirect forms to the coal surface mines operation. The direct impact on the operation with changing weather trends of extreme rainfall will increase operation delays and decrease company revenue. The indirect impact would be potential carbon tax policy implementation that puts carbon pricing on the emission generated by high fossil fuel usage, increasing the company mining cost. The company’s profitability will be at risk in the current condition if there are no efforts to minimize the impact.